A clinical trial of enteral Levetiracetam for acute seizures in pediatric cerebral malaria - Gretchen L. Birbeck; Susan T. Herman; Edmund V. Capparelli; Fraction K. Dzinjalamala; Samah G. Abdel Baki; Macpherson Mallewa; Neema M. Toto; Douglas G. Postels; Joseph C. Gardiner; Terrie E. Taylor; Karl B. Seydel (BMC, 2019)
Abstract Background Acute seizures are common in pediatric cerebral malaria (CM), but usual care with phenobarbital risks respiratory suppression. We undertook studies of enteral levetiracetam (eLVT) to evaluate pharmacokinetics (PK), safety and efficacy including an open-label, randomized controlled trial (RCT) comparing eLVT to phenobarbital. Methods Children 24-83 months old with CM were enrolled in an eLVT dose-finding study starting with standard dose (40 mg/kg load, then 30 mg/kg Q12 hours) titrated upward until seizure freedom was attained in 75% of subjects. The RCT that followed randomized children to eLVT vs. phenobarbital for acute seizures and compared the groups on minutes with seizures based upon continuous electroencephalogram. Due to safety concerns, midway through the study children allocated to phenobarbital received the drug only if they continued to have seizures (either clinically or electrographically) after benzodiazepine treatment. Secondary outcomes were treatment failure requiring cross over, coma duration and neurologic sequelae at discharge. PK and safety assessments were also undertaken. Results Among 30 comatose CM children, eLVT was rapidly absorbed and well-tolerated. eLVT clearance was lower in patients with higher admission serum creatinine (SCr), but overall PK parameters were similar to prior pediatric PK studies. Within 4 h of the first dose, 90% reached therapeutic levels (> 20 μg/mL) and all were above 6 μg/mL. 7/7 children achieved seizure freedom on the initial eLVT dose. Comparing 23 eLVT to 21 phenobarbital patients among whom 15/21 received phenobarbital, no differences were seen for minutes with seizure, seizure freedom, coma duration, neurologic sequelae or death, but eLVT was safer (p = 0.019). Phenobarbital was discontinued in 3/15 due to respiratory side effects. Conclusion Enteral LVT offers an affordable option for seizure control in pediatric CM and is safer than phenobarbital. Trial registration NCT01660672. NCT01982812.